In vitro dendrobium orchid (Dendrobium sp.) plantlet growth in different concentration of BAP and NAA - Siti Sakina; Syaiful Anwar; Florentina Kusmiyati (Jurnal Pertanian Tropik, 2019)
In vitro dendrobium orchid plantlet growth is highly determined by the cytokinin and auxin concentration. The aim of this research was to study the effect of 6-Benzylaminopurine (BAP) and Naphthaeeneacetic Acid (NAA) on growth of Dendrobium orchid plantlet. The research was arranged in completely randomized design (CRD) with two treatments. The first treatment was the concentration of BAP (A1 : 0 ppm, A2 : 1 ppm, A3 : 2 ppm) and the second treatment was the concentration of NAA (B0 : 0 ppm, B1 : 0,25 ppm, B2 : 0,50 ppm) with 4 replications. The observed variables were number of buds, plantlet height, number of leaves, and length of leaves. The data obtained were analyzed by Analysis of Variance and followed by Least Significance Different (LSD). The result showed that treatment of BAP and NAA only significantly affected the number of buds variable. The combination of BAP 1 ppm and NAA 0,25 ppm was the best treatment for increasing number of buds of dendrobium orchid plantlet.